2022
DOI: 10.5539/gjhs.v14n2p63
|View full text |Cite
|
Sign up to set email alerts
|

Myths about Coronavirus: A Research Defense

Abstract: The discovery of coronavirus is a state-of-the-art scientific study, so there is no doubt in the whole world that it is an innovation. But cybercriminals are working to create suspicion so that people are confused and afraid of the coronavirus. Cybercriminals are committing crimes from the global cloud network. They are carrying out extrajudicial killings around the world by abusing wireless sensor technology based on the victim’s active open eye, voice, adjacent sensor device and a specific GPS loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The term "green banking practices" refers to the incorporation of environmentally responsible procedures into the banking sector. The banking sector is one of the major contributors to the destruction of environment owing to significant amount of energy, resources that it consumes (Miah, Hasan, Rahman, Sharif, Uddin & Chowdhury, 2023). On other hand, new research has shed light on a number of eco-friendly banking practices that may assist the banking sector in lessening its effect on the environment and assisting with the transition to a more sustainable economic model.…”
Section: Literature Review Green Banking Practicesmentioning
confidence: 99%
“…The term "green banking practices" refers to the incorporation of environmentally responsible procedures into the banking sector. The banking sector is one of the major contributors to the destruction of environment owing to significant amount of energy, resources that it consumes (Miah, Hasan, Rahman, Sharif, Uddin & Chowdhury, 2023). On other hand, new research has shed light on a number of eco-friendly banking practices that may assist the banking sector in lessening its effect on the environment and assisting with the transition to a more sustainable economic model.…”
Section: Literature Review Green Banking Practicesmentioning
confidence: 99%
“…Studies have shown that the current crisis is a severe man-made climate crisis due to misuse of advanced satellite technology, resulting in flash-floods, cyclones, tornadoes, landslides, heat waves and epidemic diseases. Although most people in the world are not aware of these abuses, they are all closely related to advanced technology and are limited in knowledge , , , , Miah et al (2022), ]. The only way out of this crisis is to ensure secure wireless sensor networks everywhere, enabling safe use, control of GPS sensors and effective global navigation satellite systems.…”
Section: Man-made Flash Flood Devastationmentioning
confidence: 99%
“…Man-made technological pandemics are COVID-19 , Miah et al (2022), Miah et al (2021h) , cardiac arrest Miah et al (2022b), acute respiratory distress syndrome (ARDS) Miah et al (2022a), dengue and cancer etc. The climate crisis has provided insight into Earth system responses to external electromagnetic and gravitational forcing , Osman (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Pandemic coronavirus is a lesson for all of us, which history will bear witness to present and future generations Miah et al (2021) Advanced research has proven that the coronavirus was created by misuse of advanced wireless sensor technology Miah et al (2020), Miah et al (2021a), Miah et al (2021c), Miah et al (2021d), Miah et al (2021f), Miah et al (2021h), Miah et al (2022), Miah et al (2022a), Miah (2018), Miah et al (2022b), Parisha et al (2022), Miah et al (2022f), Miah et al (2022d), Miah et al (2021h). The invention of new wireless sensor technology took civilization to the golden pinnacle of progress for human well-being, thus mobilizing the nation Miah et al (2021d).…”
Section: Introductionmentioning
confidence: 99%
“…But some cybercriminals are misusing this technology to extrajudicially kill people and animals in a dark environment through digital poisoning. Miah et al (2022), Miah et al (2022b). That's when cybercriminals are promoting on social media that people around the world have died from the pandemic coronavirus disease Miah et al (2021f).…”
Section: Introductionmentioning
confidence: 99%